Pembelajaran Tongkat Berjalan (Talking Stick): Adakah Pengaruhnya Terhadap Hasil Belajar IPS Siswa? - Widiyawati Widiyawati; Yati Yati; Abdul Sholeh (Sekolah Tinggi Agama Islam Pati, 2022)
This study aims to determine whether there is an effect of talking stick learning on social studies learning outcomes for geographical characteristics and natural features of Indonesia. This research is a quantitative experimental research with a pretest posttest control group research design. The independent variable in this study is the walking stick learning model, while the dependent variable is learning outcomes. The population in this study was the fifth grade students of SD Negeri 2 Setu Kulon, Weru District, Cirebon Regency as many as 56 students. The sampling technique used a saturated sample, the experimental class was 28 students and the control class was 28 students. Data collection techniques through observation, interviews, and documentation. The research instruments used were tests and questionnaires. Data analysis used the n-gain test and t-test with a significant level of 5% using the SPSS application. The results of the questionnaire showed that 94% of students had a positive response and 6% had a negative response to the walking stick learning model which was categorized as Very Strong. The results of the t test are tcount (4.985) ttable (1.706) then H1 is accepted. This proves that there is an influence of the walking stick learning model on the social studies learning outcomes for the material on Geographical Characteristics and Natural Appearance of Indonesia.